Evolution theoretical and methodological approaches to research industry market - Ignatyuk А. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Systematization of the theoretical and methodological approaches of markets analysis was done in order to identify current research subject of industrial organization theory.